Malaysia : Staff Report for the 2011 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2012)
This 2011 Article IV Consultation reports that Malaysia's economy is vulnerable to a prolonged downturn in advanced economies or a sharp escalation in global financial stress. Weaker exports and terms of trade would spillover into domestic demand. Financial spillovers could include a reversal of cross-border bank and portfolio flows. Healthy financial and corporate balance sheets, ample foreign exchange reserves, and room to further loosen monetary policy would help contain the impact of an external shock on the financial sector and the economy.